Morphological and molecular characterization of actinic lentigos reveals alterations of the dermal extracellular matrix4. (16th November 2017) - Warrick, E.; Duval, C.; Nouveau, S.; Bastien, P.; Piffaut, V.; Chalmond, B.; Ortonne, J‐P.; de Lacharrière, O.; Bernerd, F.
Summary: Background: Actinic lentigos (AL) are benign hyperpigmented skin lesions associated with photoageing. Despite their high prevalence, biological mechanisms driving their formation remain unclear. Objectives: To provide new insights about the physiopathology of AL through a comprehensive description of their histological and molecular features. Methods: Quantitative analysis of dermoscopic images was used to select AL containing elongated patterns, predicted to display a highly deformed dermal–epidermal junction (DEJ), on the back of the hands of 15 Caucasian women. Biopsies from lesional and adjacent nonlesional (NL) areas were processed for histological analysis or gene expression profiling. Results: Histological staining confirmed a drastic deformation of the DEJ in AL, with deep epidermal invaginations into the dermis. Although the melanin content was significantly higher in AL compared with NL epidermis, the distribution of melanocytes along the DEJ was unchanged. Transcriptomic analysis revealed a signature of 529 genes differently expressed in AL vs. NL skin. Alteration of epidermal homeostasis was confirmed by the dysregulation of keratinocyte proliferation and differentiation markers. Surprisingly, canonical genes involved in melanogenesis were not significantly modulated in AL. A striking finding was the overexpression of a large group of genes involved in dermal extracellular matrix organization and remodelling. Dermal alterations were confirmed by immunolabellings on AL and NL sections. Conclusions: Drastic disorganization of the cutaneous structure in AL is accompanied by a specific molecular signature revealing alterations in both epidermal and dermal compartments. In particular, our results suggest that local modifications of the dermal extracellular matrix might contribute to hyperpigmentation in AL. Abstract : What's already known about this topic? Actinic lentigos (AL) are among the most frequent hyperpigmented lesions found in photoaged skin. Epidermal alterations and activation of melanocytes have been described in AL. What does this study add? This is the first comprehensive analysis of morphological and molecular changes in AL selected on quantitative dermoscopic criteria. A local reorganization of photodamaged dermal extracellular matrix could contribute to the impairment of keratinocyte proliferation and differentiation during AL formation. What is the translational message? To develop efficient treatment for AL, the multiple epidermal and dermal alterations associated with these lesions should be considered, rather than targeting melanocytes alone. Linked Comment:Langton. Br J Dermatol 2017;177 :1479–1480 . Plain language summary available online Respond to this article